KNOWLEDGE, PERCEPTION AND BEHAVIOR OF THE COMMUNITY BATU MERAH RIVER IN AMBON CITY REGARDING CLEANLINESS AND COMMUNITY USED OF THE RIVER - Ode, Nursida; Melay, Stevin; Liline, Sintje (RUMPHIUS, 2022)
This study aims to find out how the knowledge, perceptions and behavior of the people around the batu merah riverbanks in Ambon city about cleanliness and river utilization for the community.This research is a type of descriptive. This research involved the Batu Merah community in Ambon City. The research data were analyzed using a Likert scala.The results showed that the results of data analysis from the knowledge of the batu merah village community obtained 4,96%, community perception obtained 3,17% and the behavior of the batu merah community 2,35%. The behavior of Batu merah community regarding cleanliness and river utilization for the batu merah community in ambon city is lower than knowledge and perception.